A high-capacity of oxygen induced SrTiO3 cathode material for rechargeable Alkaline Zinc battery. (1st August 2021) - Wong, Christelle Pau Ping; Lai, Chin Wei; Lee, Kian Mun; Pan, Guan Ting; Chong, Kok Boon; Johan, Mohd Rafie; Juan, Joon Ching; Yang, Thomas Chung Kuang
Abstract: The tremendously usage in batteries has led to development of safe, economical and environment friendly batteries. Therefore, the progress to explore new type of battery such as rechargeable alkaline zinc batteries (RAZBs) based on metal oxides has attracted many interests. In this study, RAZBs based on SrTiO3 nanoparticles as cathode is successfully produced and also managed to generate high specific volume capacity of 387 mAh cm −3 at 1.2 V. Based on the total volume of battery, the energy density of the battery is 37 mWh cm −3 . The SrTiO3 prepared via facile hydrothermal process exhibits large specific surface area. Besides the surface area, the presence of oxygen vacancies (V o ¨ ) in SrTiO3 is also contributed to the high electron contact efficiency. The presence of V o ¨ play an important role in the redox property and rechargeability of SrTiO3 as cathode. The RAZBs based on SrTiO3 nanoparticles shows a good cycling performance and achieve 100% coulombic efficiency. In conclusion, the new cathode material based on SrTiO3 create new possibilities for RAZBs. Graphical abstract: Image 1 Highlights: Cathode based on SrTiO3 nanoparticles is prepared by facile hydrothermal method. The RAZBs of Zn//SrTiO3 battery delivers a high discharge capacity of 387 mAh cm −3 . Redistribution of V o ¨ is responsible for redox reactions of SrTiO3 in RAZBs. Zn//SrTiO3 battery achieves the energy density of 37 mWh cm −3 . Good cyclability and coulombic efficiency of RAZBs based on SrTiO3 perovskite.